2018
DOI: 10.1177/1753495x18799569
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia during pregnancy: Review of maternal and fetal complications, investigations, and management

Abstract: Introduction Asymptomatic mild primary hyperparathyroidism is increasingly being identified during pregnancy. Recent studies have demonstrated inconsistent findings with regard to pregnancy complications and the need for surgical intervention during pregnancy. Method A retrospective audit of outcomes of pregnancies complicated by hypercalcaemia over a 15-year period was performed. Results Twenty-nine pregnancies to 26 women with hypercalcaemia were identified, corresponding to 37 cases per 100,000 deliveries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…For pregnant patients with PHPT with asymptomatic, mildly elevated, serum calcium levels or patients who do not accept surgery, close observation without surgical intervention is feasible [ 19 , 20 ]. The first-line medication is oral or intravenous rehydration with or without furosemide, which is safe, can avoid iatrogenic placental hypoperfusion or oligohydramnios caused by dehydration [ 21 ] and will not increase the risk of obstetric complications, such as abortion.…”
Section: Discussionmentioning
confidence: 99%
“…For pregnant patients with PHPT with asymptomatic, mildly elevated, serum calcium levels or patients who do not accept surgery, close observation without surgical intervention is feasible [ 19 , 20 ]. The first-line medication is oral or intravenous rehydration with or without furosemide, which is safe, can avoid iatrogenic placental hypoperfusion or oligohydramnios caused by dehydration [ 21 ] and will not increase the risk of obstetric complications, such as abortion.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of characterized symptoms of PHPT during pregnancy is another reason for the misdiagnosis. A previous study of women with severe symptomatic hypercalcemia in pregnancy showed a significantly higher risk of developing maternal-fetus complications [4] . Deteriorating hypercalcemia may cause a hypercalcemic crisis during pregnancy, a life-threatening complication to both mother and fetus.…”
Section: Introductionmentioning
confidence: 94%
“…A previous study of women with severe symptomatic hypercalcemia in pregnancy showed a significantly higher risk of developing maternal-fetus complications. [ 4 ] Deteriorating hypercalcemia may cause a hypercalcemic crisis during pregnancy, a life-threatening complication to both mother and fetus. Therefore, early diagnosis and treatment of PHPT are critical.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of ultrasound is lower in multiglandular disease and may be only 15-35% [77,78]. Magnetic resonance imaging (MRI) can be used [79], however, it has a sensitivity of 82% [80] in detecting parathyroid adenoma and should not be used as a single imaging modality in localizing parathyroid adenoma [81]. MRI with gadolinium contrast should be limited in pregnancy since this agent is water-soluble and may cross the placenta [82].…”
Section: Localizationmentioning
confidence: 99%